Investigation on the effect of reciprocating sliding wear test for titanium alloy, Ti-6Al-4V under frequency set up - Mohd Harun, Dalila; Mohd Tobi, A L; Jamian, Saifulnizan (WARSE, 2020)
Reciprocating sliding wear test of uncoated titanium alloy, Ti-6Al-4V is investigated using pin-on-flat arrangement under variables of reciprocal frequency set up (1, 2 and 2.5 Hz) for contact pin Ø6.5 mm. Frictional force resulted 60 – 80 N tangential force in range and the graph pattern for COF resulted running-in condition at earlier second and highest peak experienced in value 0.45-0.48 in range. The micrography shows more sticking at the end of the wear track and significant at parameter 1 Hz frequency. The profilometry shows the result of wear width and wear area where the wear width is increasing with the increasing of frequency set up while wear area decreasing with the increasing of frequency. The hardness shows high value for 2.5 Hz. The cyclic plasticity presence is examined using Scanning Electron Microscope (SEM). The black spot present at the end of wear track are identified as an accumulation of ploughing during sliding and approved by the hardness result where the accumulation part experienced highest value 962 HV. This value proved that plastic deformation is formed during the sliding with the adhesive and abrasive mechanism.